Implementasi Keterampilan Berpikir HOTS pada Soal Asesmen Bahasa Indonesia di Madrasah Aliyah - Purwaningsih, Herni; Widayati, Mukti; Nurnaningsih, Nurnaningsih (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This study aims to describe the implementation of HOTS thinking skills in madrasah assessment problems based on material, construction, and language as well as Bloom's Taxonomy C4 (analyzing), C5 (evaluating), and C6 (creating). This research is descriptive qualitative research. Methods used interviews and documentation. The sources of this research data are teachers and students as well as documents on the assessment of madrasah Indonesian at MAN 1 Gunungkidul. The data validity test technique uses triangulation of sources and methods. Data was analyzed using the Miles and Huberman model stages. The results showed that the preparation of madrasah assessment questions was in accordance with the steps for preparing higher order thinking questions (HOTS). Based on the material analysis, 25 questions have fulfilled the material aspects in writing HOTS questions, 8 questions on one aspect have not been fulfilled, 7 questions have not been fulfilled on two aspects. Based on the construction of the questions, 5 questions meet the construction aspect, 2 questions one aspect is not fulfilled, 29 questions two aspects are not met, 4 questions three aspects are not met. Based on Language, as many as 29 questions meet the Language aspect, 11 questions do not meet. Based on Bloom's Taxonomy, the cognitive domain used is mostly the C4 cognitive level (analyzing). Based on 40 questions, 28 (70%) questions including the realm of analyzing (C4), the realm of evaluating (C5), and creating (C6) were not found. A total of 12 (30%) questions falls into the C3 question category.